A Heat transfer textbook - Lienhard, John H. (Phlogiston Press, 2008)
This textbook is an introduction to heat and mass transfer oriented toward engineering students. The subjects covered include heat conduction, forced and natural convection, thermal radiation, boiling, condensation, heat exchangers, and mass transfer. The book includes worked examples and end-of-chapter exercises. This revised printing of the third edition includes a variety of updates and corrections.